2000
DOI: 10.1038/sj.cdd.4400622
|View full text |Cite
|
Sign up to set email alerts
|

Antibody mAb33 from Transduction Laboratories detects human CD95L in ELISA but not in immunoblots

Abstract: The expression and function of CD95 ligand (CD95L, FasL, Apo-1L) in normal and pathological immune responses are subject of extensive studies. The analysis of CD95L protein expression relies on antibodies specific for CD95L. Testing CD95L expression by immunoblotting using the monoclonal antibody 33 from Transduction Laboratories (Lexington, KY, USA) raised against CD95L we found CD95L protein in many different cell types even if CD95L transcripts were undetectable by RT ± PCR. Because of these contradictory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 3 publications
1
6
1
Order By: Relevance
“…7 Finally, in 2D electrophoresis, mAb 33 detected a protein with different mobility than the CD95L specific signal detected by G247-4 and a polyclonal rabbit anti-CD95L antibody, PE62. 9 In our present study, mAb33 did not only stain CD95L-transfected and control cells to a similar extent, but also strongly labeled tonsillar epithelial cells in tissue sections which lacked CD95L mRNA by in situ hybridization. Even though there may be differences in binding properties under reducing and non-reducing conditions, 9,13 our findings support the assumption by Fiedler and co-workers 9 that mAb 33 most probably detects a protein different from CD95L.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…7 Finally, in 2D electrophoresis, mAb 33 detected a protein with different mobility than the CD95L specific signal detected by G247-4 and a polyclonal rabbit anti-CD95L antibody, PE62. 9 In our present study, mAb33 did not only stain CD95L-transfected and control cells to a similar extent, but also strongly labeled tonsillar epithelial cells in tissue sections which lacked CD95L mRNA by in situ hybridization. Even though there may be differences in binding properties under reducing and non-reducing conditions, 9,13 our findings support the assumption by Fiedler and co-workers 9 that mAb 33 most probably detects a protein different from CD95L.…”
Section: Discussionsupporting
confidence: 78%
“…Specificity of the monoclonal CD95L antibody 33 has first been doubted when CD95L was found in normal thyrocytes in Western blots using mAb 33 although they lacked detectable CD95L mRNA in both RT ± PCR and nuclease protection assays. 6 Fiedler et al 7,9 reported that, in immunoblots, mAb 33 detected an identical 37 kDa signal in both CD95L-transfected and untransfected 293T cells while, using mAb G247-4, only transfected cells showed a CD95L-specific signal. Moreover, mAb 33 did not recognize immunoprecipitated CD95L from transfected 293T cells, but a 37 kDa protein in the supernatant of the immunoprecipitate.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms the findings reported by Rezai et al [6], Farrokh-Siar et al [7] and Ferguson and Griffith [1] using cultured human and murine RPE cells. It contradicts the results of a recent study by Jiang et al [13] where cultured human RPE cells p (6) [5], and that the specificity of the anti-FasL antibody (C-33) applied in immunoblotting has been put in question [14][15][16]. Additionally, the RT-PCR reported by Jiang et al [13] lacks a positive control.…”
Section: Discussioncontrasting
confidence: 55%
“…54 • Finally, a great deal of confusion was caused by a number of reports that used antibodies of questionable CD95L specificity. [59][60][61] Although a recent editorial suggested that certain anti-CD95L antibodies should be removed from the market, 59 such antibodies have been some of the most widely used reagents for immunohistochemical detection of CD95L.…”
Section: Cd95 In Uc: Yesterday and Todaymentioning
confidence: 99%